History-writing, communication and the making of political connections in Italy, c. 1270-1347 - Bain, S (2024)
This thesis examines urban political culture and geopolitical developments in later thirteenth- and early fourteenth-century Italy by investigating the relationship between history-writing and other forms of ‘political communication’: the processes by which political information, values and practices were transmitted, preserved and perpetuated. The period saw the political reshaping of the peninsula. Descendants of Charles of Anjou (d. 1285), supported by the Papacy, fought with both the Catalan-Aragonese and claimants to the Holy Roman Empire for supremacy in Sicily and the Italian peninsula, while strife in the city-communes was articulated through ‘Guelf’ and ‘Ghibelline’ identities constructed around this broader conflict. To negotiate these struggles, contemporaries produced and stored in increasing quantities different forms of written communication, e.g., letters, political sermons and collections of treaties and charters. This thesis shows how we can understand these political developments and the communications around them through the concurrent boom in urban history-writing.